PENGARUH SUBSTITUSI SARI KACANG KOMAK (LABLAB PURPUREUS (L.) SWEET) DAN SUSU SKIM TERHADAP SIFAT ORGANOLEPTIK, NILAI PH, DAN TOTAL BAKTERI ASAM LAKTAT YOGHURT KACANG KOMAK - Astrid Widiastuti; Judiono Judiono (Universitas Airlangga, 2017)
Lablab bean has potential as alternative food subtituteof soybean Lablab Bean has nutrients content which is not much different, but fatcontent is much lower than soybean. Yogurt is milk fermented by the lactic acid bacteria Streptococcus thermophilusand Lactobacillus bulgaricusthat tranformmilk sugar (lactose) into lactic acid to obtain acidity, smell, and speciﬁ c ﬂ avor. The aim of this research was to study the effect of substitution of lablab bean milk and skim milk to organoleptic properties, pH value, and the total of lactic acid bacteria (LAB). The Experimental design was appliedusing completely randomized design with 30 untrained panelists. The research conducted in three treatments with two repetitions. The data collected are total LAB and pH value. The organoleptic properties test used was hedonic quality test with one repitition. The pH value was measured using an electronic pH meter. The total of LAB was measuredusing Man Rogosa and Sharpe (MRS) media. The level of lactic acid was measured using acidity test. The treatment applied was the effect of substitution of lablab bean milk 92%, 95%, and 96,5%, and skim milk 8%, 5%, and 3,5%. Data were analyzed with Anova, Kruskal Wallis, Duncan Multi Range with signiﬁ cance level p < 0,05. The result showedthat organoleptic properties ofsubstituion 92:8 is closer to the expected quality ofyoghurt with the lowest pH value, and the highest pH value is substitution96,5 :3,5. The measurement results of the total LAB and lactic acid levels showed the substitution 92:8 has the highest value and the substitution of 96,5:3,5 has the lowest value. The result of Microscopic on Gram staining showed that Streptococcus thermopillus and Lactobacillus bulgaricus bacteria were found in lablab beans yoghurt. This result indicates that the lablab bean can be potentially used as the main material to make yoghurt.